(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The investigated Mt. Zrinska Gora amphibolites are a part of the metamorphic sole of the Banovina ophiolite complex. Mineral composition and other petrographic characteristics of amphibolites and adjacent peridotite were investigated by polarised microscopy and chemical analyses of rocks were obtained by a combination of inductively coupled plasma mass and emission spectrometry. The main minerals in these garnet-bearing amphibolites are amphibole and plagioclase with accessory garnet, sphene, spinel, opaque mineral ± clinopyroxene ± quartz ± actinolite ± zoisite-clinozoisite ± prehnite ± pumpelyite and ± clay minerals. Kelyphitic corona is developed around garnet. The amphibolites have nematoblastic, nematogranoblastic, porphyroblastic and porphyroclastic textures and homogenous to foliated structures. The presence of clinopyroxene in some of the investigated amphibolites points to their possible formation under P‒T conditions of upper amphibolite facies. The greenschist facies retrograde metamorphism and subsequent surface weathering of amphibolites is also evident. The chemical composition of rocks indicates that protoliths of most amphibolites were tholeiitic basalts, initially formed in island arcs and the adjoining back-arc basins. During the intraoceanic subduction in Jurassic Neotethys Ocean basalts/basaltic tuffs of island arc tholeiite affinity and back-arc basin basalts, positioned on the top of the down-going oceanic slab, were welded to the base of the hot over-riding mantle wedge, metamorphosed to amphibolite rocks and obducted together with ophiolites on the Adria continental margine. The new described amphibolite type having peridotite protolith characteristics originated as the consequence of the hydration of the bottom part of the overlying mantle wedge.